Modelling the immunopathogenesis of HIV-1 infection and the effect of multidrug therapy: The role of fusion inhibitors in HAART - Gesham Magombedze; Winston Garira; Eddie Mwenje (Mathematical Biosciences and Engineering)
There is currently tremendous effort being directed at developingpotent, highly active antiretroviral therapies that can effectively control HIV-1 infection without the need for continuous, lifelong use of these drugs. Inthe ongoing search for powerful antiretroviral agents that can affect sustainedcontrol for HIV infection, mathematical models can help in assessing both thecorrelates of protective immunity and the clinical role of a given drug regimen aswell as in understanding the efficacy of drug therapies administered at differentstages of the disease. In this study, we develop a new mathematical model ofthe immuno-pathogenesis of HIV-1 infection, which we use to assess virologicalresponses to both intracellular and extracellular antiretroviral drugs. We firstdevelop a basic mathematical model of the immuno-pathogenesis of HIV-1infection that incorporates three distinct stages in the infection cycle of HIV-1:entry of HIV-1 into the cytoplasm of CD4+ T cells, transcription of HIV-1RNA to DNA within CD4+ T cells, and production of HIV-1 viral particleswithin CD4+ T cells. Then we extend the basic model to incorporate the effectof three major categories of anti-HIV-1 drugs: fusion/entry inhibitors (FIs),reverse transcriptase inhibitors (RTIs), and protease inhibitors (PIs). Modelanalysis establishes that the actual drug efficacy of FIs, γ and of PIs, κ isthe same as their effective efficacies while the effective drug efficacy for theRTIs, γ εis dependent on the rate of transcription of the HIV-1 RNA to DNA,and the lifespan of infected CD4+ T cells where virions have only entered thecytoplasm and that this effective efficacy is less than the actual efficacy, ε. Ourstudies suggest that, of the three anti-HIV drug categories (FIs, RTIs, andPIs), any drug combination of two drugs that includes RTIs is the weakest inthe control of HIV-1 infection.